2018
DOI: 10.1088/1361-6579/aadeff
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and reduction of exercise-based motion influence on heart rate variability using accelerator signals and channel decoding in the time–frequency domain

Abstract: In our proposed method, we utilized the motion trajectory (which is known to exist partially in HRV) measured by a three-channel accelerator (ACC). We then estimated their shares in HRV using a wearable electrocardiogram (ECG) and an error-correcting problem formulation. In this method, we characterized the motion components of three orthogonal directions induced into the HRV signal, and then we suppressed the estimated motion artefact to construct a motion-attenuated spectrogram. Main results and Significance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Since with wearable devices such as Faros, the experimental conditions differ and are not always performed in a controlled laboratory environment, the gathered data can be affected by motion artefacts. Alikhani et al found that motion can describe the high frequencies in HRV up to 40% [68]. However, the noise of motion can be eliminated by adding an additional accelerometer on each electrode [69].…”
Section: Introductionmentioning
confidence: 99%
“…Since with wearable devices such as Faros, the experimental conditions differ and are not always performed in a controlled laboratory environment, the gathered data can be affected by motion artefacts. Alikhani et al found that motion can describe the high frequencies in HRV up to 40% [68]. However, the noise of motion can be eliminated by adding an additional accelerometer on each electrode [69].…”
Section: Introductionmentioning
confidence: 99%